Polymorphisms in genes expressed during amelogenesis and their association with dental caries: a case-control study - Gachová, Daniela; Lipovy, Bretislav; Deissova, Tereza; Izakovicova Holla, Lydie; Danek, Zdenek; Borilova Linhartova, Petra (Clinical oral investigations, 2023)
OBJECTIVES: Dental caries is a widespread multifactorial disease, caused by the demineralization of hard dental tissues. Susceptibility to dental caries is partially genetically conditioned; this study was aimed at finding an association of selected single nucleotide polymorphisms (SNPs) in genes encoding proteins involved in amelogenesis with this disease in children. MATERIALS AND METHODS: In this case-control study, 15 SNPs in ALOX15, AMBN, AMELX, KLK4, TFIP11, and TUFT1 genes were analyzed in 150 children with primary dentition and 611 children with permanent teeth with/without dental caries from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) cohort. RESULTS: Dental caries in primary dentition was associated with SNPs in AMELX (rs17878486) and KLK4 (rs198968, rs2242670), and dental caries in permanent dentition with SNPs in AMELX (rs17878486) and KLK4 (rs2235091, rs2242670, rs2978642), (p ≤ 0.05). No significant differences between cases and controls were observed in the allele or genotype frequencies of any of the selected SNPs in ALOX15, AMBN, TFIP11, and TUFT1 genes (p > 0.05). Some KLK4 haplotypes were associated with dental caries in permanent dentition (p ≤ 0.05). CONCLUSIONS: Based on this study, we found that although the SNPs in AMELX and KLK4 are localized in intronic regions and their functional significance has not yet been determined, they are associated with susceptibility to dental caries in children. CLINICAL RELEVANCE: AMELX and KLK4 variants could be considered in the risk assessment of dental caries, especially in permanent dentition, in the European Caucasian population.
Keywords: studie případů a kontrol; dítě; longitudinální studie; lidé; Longitudinal Studies; zubní kaz; amelogenin; Amelogenin; Amelogenesis; amelogeneze; Child; Case-Control Studies; Humans; Dental Caries